Recurrent pericardial effusion in a boy: A clue to underlying pericardial and pulmonary lymphangiectasia - Deepanjan Bhattacharya; Arun Gopalakrishnan; Deepa Sasikumar; Anoop Ayyappan; Harikrishnan K N Kurup; Sabarinath Menon; Kavasseri M Krishnamoorthy (Wolters Kluwer Medknow Publications, 2022)
Pulmonary lymphangiectasia is a rare congenital malformation of lymphatic vessels. We report the case of a 5-year-old boy with recurrent pericardial effusion which was diagnosed to be due to pericardial and pulmonary lymphangiectasia.